Ali je Ustavno sodišče vezano na svoje odločitve? - Sotošek, David (Pravnik, 2023)
The aim of this article is to explore whether the Constitutional Court of the Republic of Slovenia is legally bound by its own decisions. First, the author distinguishes two alternative conceptions of how past judicial decisions may be relevant to the decision-making of a later court. On the first account, the court is bound by a previous decision in the sense of only being permitted to depart from it when reasons of special kind or weight obtain, not whenever it deems that decision wrong. On the second view, the court has more latitude: it may always change its mind on a legal issue as long as it provides a reasonable justification for doing so. In the remainder of the article, the author evalu- ates three arguments in favour of the claim that the first view most faithfully describes the attitude which the Constitutional Court legally ought to adopt towards its own decisions.
Keywords: ovrženje; precedens; sodišča; sodna praksa; Ustavno sodišče; ustavnosodne odločitve; varstvo pravic